2016
DOI: 10.1021/acs.joc.6b00860
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of Bismuth(V)-Mediated Thioglycoside Activation Reveal Differential Reactivity of Anomers

Abstract: The mechanism of bismuth(V)-mediated thioglycoside activation was examined using reaction kinetics and quantum chemical reaction models. NMR experiments show an unusual nonlinear growth/decay curve for the glycosylation reaction. Further studies suggest an anomeric inversion of the β-glycoside donor to the α-donor during its activation, even in the presence of a neighboring 2-position acetate. Interestingly, in situ anomerization was not observed in the activation of an α-glycoside donor, and this anomer also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…In a study of the triphenylbismuth ditriflate promoted reactions of ethyl 2,3,4,6-tetra- O -benzyl-β-D-thiogalactopyranoside Pohl and coworkers found that epimerization to the α-anomer preceded the actual glycosylation reaction. Moreover, albeit the actual mechanism of activation is unclear in view of the lengthy induction periods observed, it was found that the α-anomer was the more reactive of the two under the reaction conditions described, 182 thereby drawing attention to the fact that equatorial glycosides are not necessarily more reactive than their axial counterparts in all instances. Indeed, a subsequent study by Zhu and coworkers comparing the relative reactivities of the two anomers of a set of glucopyranosyl thioglycosides under NIS/TMSOTf activation revealed an interesting albeit unexplained dependence on the protecting group pattern and configuration (Figure 13).…”
Section: Generation and Characterization Of Covalently-bound Activamentioning
confidence: 96%
See 1 more Smart Citation
“…In a study of the triphenylbismuth ditriflate promoted reactions of ethyl 2,3,4,6-tetra- O -benzyl-β-D-thiogalactopyranoside Pohl and coworkers found that epimerization to the α-anomer preceded the actual glycosylation reaction. Moreover, albeit the actual mechanism of activation is unclear in view of the lengthy induction periods observed, it was found that the α-anomer was the more reactive of the two under the reaction conditions described, 182 thereby drawing attention to the fact that equatorial glycosides are not necessarily more reactive than their axial counterparts in all instances. Indeed, a subsequent study by Zhu and coworkers comparing the relative reactivities of the two anomers of a set of glucopyranosyl thioglycosides under NIS/TMSOTf activation revealed an interesting albeit unexplained dependence on the protecting group pattern and configuration (Figure 13).…”
Section: Generation and Characterization Of Covalently-bound Activamentioning
confidence: 96%
“…The question of in situ anomerization of donors is one that is not limited to the anomeric halides and one that is frequently invoked in discussions of mechanism. 180,182 Actual studies of the rate of anomerization as compared to the overall rate of glycosylation are however sparse. Recently, D’Angelo and Taylor provided a solution to this problem in the form of NMR exchange spectroscopy (EXSY).…”
Section: Generation and Characterization Of Covalently-bound Activamentioning
confidence: 99%
“…However, these thiophilic promoters are generally incompatible with alkenes and/or alkynes, thereby limiting the use of these common handles in synthetic schemes. Gold trichloride and triphenylbismuth ditriflate ( 1 ) have been shown to tolerate double bondsand triple bonds in the case of the bismuth reagentbut both reagents still have issues that limit their use. For example, gold trichloride is very hygroscopic, and the pentavalent bismuth promoter, although easily handled in air, is slow to activate sugars with many electron-withdrawing groups.…”
mentioning
confidence: 99%
“…Recent mechanistic studies of these pentavalent-bismuth-mediated glycosylations of alkyl thioglycosides showed that these reactions undergo an initial lag phase . Interestingly, this lag phase can be shortened with the addition of a propanethiol additive, which dramatically increases the rate of glycosylation .…”
mentioning
confidence: 99%
“…16 The toughest manual separations in our labs have been the products of chiral sugars linked to achiral components. Therefore, a reaction mixture resulting from glycosylation of a chiral thioglycoside 17 with an achiral fluorous tag (see ESI† for more details) was subjected to our R-HPLC (Fig. 3) conditions with a PFP column given that this stationary phase was best suited for aromatic protecting group containing carbohydrates.…”
mentioning
confidence: 99%